BS EN IEC 61557-17. Electrical safety in low voltage distribution systems up to 1 000 V a.c. and 1 500 V d.c. Equipment for testing, measuring or monitoring of protective measures. Part 17. Non-contact voltage indicators (8th November 2019) - British Standards Institution,
No abstract available